Characteristics and management of occult intrasacral extradural cyst in children. (August 2013) - Huang, S.-L.; Jiang, H.-X.; Cheng, B.; Ning, N.; He, X.-J.
Abstract: Occult intrasacral extradural cyst is a rare entity. Since little about this lesion has been reported in the literature, this study herein demonstrates by cases some of the clinical features and surgical treatment of occult intrasacral extradural cyst in children. A series of 4 children, 2 boys and 2 girls aged from 4 years and 6 months to 11 years, with occult intrasacral extradural cyst were reviewed. All patients underwent neurological examinations and magnetic resonance imaging. Of these 4 patients two had urinary incontinence in daytime, one frequent micturition, and one numb in saddle area. There were no abnormal findings on physical or laboratory examination. Whole excision of the cyst and ligation of the tract between the cyst and thecal sac were performed for all the patients. No complications such as cerebrospinal fluid leakage and infection were found after operation. All cases made complete recovery and have been asymptomatic at follow-up. The clinical and radiological features of occult intrasacral extradural cyst are characteristic in children. Magnetic resonance imaging is the choice of investigation and surgery is curative.